Pengaruh Kemampuan Spasial Dan Komunikasi Matematis Terhadap Hasil Belajar Matematika Siswa - Eka Ayu Rasta, Ni Putu Virgi; Hikmah, Nurul; Salsabila, Nilza Humaira; Prayitno, Sudi (Mandalika Mathematics and Educations Journal, 2025)
The purpose of this study was to determine the effect of spatial intelligence and mathematical communication on the mathematics learning outcomes of class IX students of SMPN 5 Mataram in the 2024/2025 Academic Year. This type of research is quantitative with the ex post facto method. The population in this study were all class IX students of SMPN 5 Mataram in the 2024/2025 academic year with a total of 249 students. The sampling technique used probability sampling so that 1 class was selected, namely class IX B with a total of 31 students. The method of data collection was through giving tests of spatial ability, mathematical communication and mathematics learning outcomes with the material of similarity and congruence, surface area and volume of various curved and flat sided geometric shapes. The data analysis technique used in this study was descriptive statistical analysis and inferential statistical analysis. Based on the results of the inferential statistical analysis calculation, the t count value> t table was obtained, namely 6.238> 2.045 so that there was an effect of spatial ability on mathematics learning outcomes. The calculated t value > t table is 2.525 > 2.045 so that there is an influence of mathematical communication on mathematics learning outcomes. The Rxy (R) value is 0.836, sig. value 0.000 < 0.05 and 32.446 > 3.33. There is also an influence of variables X1 and X2 simultaneously on variable Y of 69.9%, which means that there is a positive influence between spatial ability and mathematical communication on students' mathematics learning outcomes with a strong relationship level. So, it can be concluded that there is an influence of spatial ability and mathematical communication on the mathematics learning outcomes of grade IX students of SMPN 5 Mataram in the 2024/2025 academic year.